Identification of Broadleaf Weed Seedlings Commonly Found in Florida Sugarcane: A Quick Reference Guide - D. C. Odero; M. VanWeelden; C. Kammerer (EDIS, 2023)
This publication describes the proper identification of broadleaf weed seedlings commonly found in Florida sugarcane fields and aims to assist growers in selecting effective control measures. Written by D. C. Odero, M. VanWeelden, and C. Kammerer, and published by the UF/IFAS Agronomy Department, March 2023.